The relationship of family functioning and self-control to religious orientation among mothers of autistic children - Atousa Kafashpour Marandi; Anahita Khodabakhshi -Koolaee (Shahid Beheshti University of Medical Sciences, 2018)
For downloading the full-text of this article please click here. Background and Objective: Self-control in religious texts is a comprehensive and unique system, which is derived from the surveillance of God upon one's actions and control of one's own actions. Since self-control in Islamic teachings plays a decisive role in human life, this study aimed to examine the correlations among family functioning, self-control and religious orientation among mothers of children with autism. Method: This descriptive correlational study used a convenience sampling technique. 100 mothers of autistic children participated in this study in years 1394 and 1395. The Participants completed 3 questionnaires: Tangney Self-control Scale, General Functioning subscale of the MC Master Family Assessment Device (FAD), and Allport Religious Orientation Scale. Data analysis was performed using multiple regression analysis and Pearson correlation coefficient. All ethical issues were observed in this research and the researchers declared no conflict of interests. Results: The findings indicated a significant positive correlation between self-control and religious orientation and also between self-control and family functioning (p<0.05). This means that the more self-control, the higher religious orientation, and vice versa. Furthermore, with increase in family functioning, self-control increased and the other way round (p<0.05). No relationship between family functioning and internal and external religious orientation was found. Conclusion: The findings of the present study highlight the relationship between religious-orientation and self-control. Therefore, preventive measures, education, and religious interventions along with self-control need to considered more than before. For downloading the full-text of this article please click here.